Os tipos micaelenses : a tipografia e as Oficinas Tipográficas da Ilha de São Miguel - Freitas, Denise Miriam Vitorino (2022)
The history and actuality of movable character typography in the context of São Miguel Island constitute the object of study of this dissertation. The origin of this printing technique on this island and its development over the last few centuries reveal a unique story to be disclosed, that has been little documented before. Thanks to current cultural initiatives that aim to give continuity to art, this subject is increasingly arousing the interest of creatives and supporters of the arts. This dissertation, in a way, intends to continue these initiatives and explores this little known field in arts and national context. It is a research based on interviews with the various museological, cultural and professional entities and personalities who have given their contribution, and on the collection and analysis of artifacts, as well as existing bibliography. The aim is to make a general survey of the printing activity on the island, from its origins to the present day, in order to promote it and make it accessible to the academic and general public.